Introduction of the Project “Community Police Officer” as a Step towards Strengthening Local Security Infrastructure - O. I. Bezpalova (Law and Safety)
The author has emphasized on the importance of strengthening the institutional capacity of local self-government agencies to address their challenges, including in the field of public safety, in particular by strengthening local security infrastructure. It has been stated that the urgent issue of the present time is to update the tools of interaction between the local population and the police to achieve a common goal – to ensure public order and safety at the regional level focused on the needs of citizens. It has been emphasized that it is currently important to use the positive foreign experience of organizing the work of the police agencies and units. On the basis of studying this experience it is advisable to implement pilot projects aimed at creating a safe environment for citizens, which should implement effective local security infrastructure. To this end, the project “Community Police Officer” was launched in 2019 as part of the reform of the National Police in Ukraine.